2020
DOI: 10.1039/c9na00667b
|View full text |Cite
|
Sign up to set email alerts
|

Spatial focusing of magnetic particle hyperthermia

Abstract: Magnetic particle hyperthermia is a promising cancer therapy, but a typical constraint of its applicability is localizing heat solely to malignant regions sparing healthy surrounding tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 59 publications
0
33
0
1
Order By: Relevance
“…The size, size distribution, and shape of a particular NM have a clear impact on its magnetic properties [ 31 ]. These parameters should ideally be optimized [ 32 ] so as to exhibit the highest heating power under a selected AMF frequency [ 33 , 34 , 35 ], while displaying minimal toxicity if not subjected to an external magnetic field. This optimization also minimizes the need to revise extrinsic parameters, such as the NM concentration or the AMF power.…”
Section: Main Parameters Influencing the Outcome Of A Preclinical mentioning
confidence: 99%
“…The size, size distribution, and shape of a particular NM have a clear impact on its magnetic properties [ 31 ]. These parameters should ideally be optimized [ 32 ] so as to exhibit the highest heating power under a selected AMF frequency [ 33 , 34 , 35 ], while displaying minimal toxicity if not subjected to an external magnetic field. This optimization also minimizes the need to revise extrinsic parameters, such as the NM concentration or the AMF power.…”
Section: Main Parameters Influencing the Outcome Of A Preclinical mentioning
confidence: 99%
“…To address this important technical challenge, several research groups have demonstrated experimentally that the MPI gradient field can localize MFH heating [21,22,[61][62][63][64]. Despite using a 300 kHz magnetic field, we and others have demonstrated localized heating to millimeter-scale resolution.…”
Section: Fundamentals Of Gradient-based Localizationmentioning
confidence: 99%
“…Encapsulin systems that biomineralize iron naturally provide an efficient means of generating magnetic nanoparticles, with promising applications in magnetic hyperthermia therapy (MHT) [87]. Clinical trials of MHT have been approved for different types of cancer using superparamagnetic iron oxide nanoparticles [126]. The EncMx system was used to generate magnetic nanoparticles, which are monodisperse, resistant to extreme pH and protease digestion, and stable when exposed to blood and serum.…”
Section: Encapsulin-based Metallic Nanoparticlesmentioning
confidence: 99%